Reducing Blindness from Retinopathy of Prematurity (ROP) in Argentina Through Collaboration, Advocacy and Policy Implementation. Issue 5 (16th April 2018) - Hariharan, Luxme; Gilbert, Clare E; Quinn, Graham E; Barg, Frances K; Lomuto, Celia; Quiroga, Ana; McLeod-Omawale, Joan; Zin, Andrea; Ortiz, Zulma; Alda, Ernesto; Bouzas, Liliana; Brussa, Marina; et al.
Abstract: Retinopathy of prematurity (ROP) is a largely avoidable cause of blindness in children worldwide, requiring high-quality neonatal care, early detection and treatment. In middle-income countries throughout Latin America, Eastern Europe and South Asia, there has been a rise in ROP blindness due to a combination of increased survival of preterm infants, resource-scarce medical environments and lack of policies, training and human resources. However, Argentina is an example of country where rates of ROP blindness have declined and ROP programmes have been successfully and effectively embedded within the health and legal system. The purpose of this study is to describe the activities and stakeholders, including Ministry of Health (MoH) and UNICEF, involved in the process, from recognition of an epidemic of ROP blindness to the development of national guidelines, policies and legislation for control. Using a retrospective mixed methods case study design, data on rates of severe ROP was collected from 13 neonatal intensive care units from 1999 to 2012, and on the proportion of children blind from ROP in nine blind schools in seven provinces. Legislative document review, focus group discussions and key informant interviews were conducted with neonatologists, ophthalmologists, neonatal nurses, parents, MoH officials, clinical societies, legislators and UNICEF officials in seven provinces. Results are presented combining the stages heuristic policy framework and Shiffman including: agenda setting, policy formulation, implementation and evaluation. By 2012, ROP had declined as a cause of blindness in children in schools for the blind as had rates of severe ROP needing treatment in the NICUs visited. Multiple factors played a role in reducing blindness from ROP in Argentina and successfully coordinating its control including national advocacy, leadership, legislation and international collaboration. Lessons learned in Argentina can potentially be scaled to other LMICs in Latin America and beyond with further context-specific research.